Conceptual Model on Internet Banking Acceptance in China with Social Network Influence - Yi, Guo; Zainuddin, Norziha Megat Mohd.; Bakar, Nur Azaliah Bt Abu (JOIV : International Journal on Informatics Visualization, 2021)
The Internet of Things and Industry 4.0 is changing the way we live including Internet Banking. Although, the government has been encouraging, the acceptance of internet banking is still not well received by Chinese customers. The reason is because they are more concerned about the economic development on the banking industry, and less concerned about technology acceptance and its development. This lack of acceptance is also attributed to the current lack of social network influence to internet banking which including its weak compliance, lack of identification, and lack of internalization. This paper aims to identify the factors that may be influencing IB acceptance by proposing a model which can determine customer’s behavioural intention based on social network influence. The TAM, UTAUT and the Social Influence Theory (SIT) were simultaneously adopted for this study. It is to use the TAM model’s perceived ease of use and perceived usefulness, the UTAUT model’s social influence, and the SIT’s compliance, identification and internalization factor for the analysis. For this purpose, a preliminary study was first administered so as to identify customers’ attitude of the IB acceptance. Thirty respondents were recruited for a structured interview. The behavioural intention and social network influence on internet banking in China was then examined with the proposed model. It appears that the model can be used to forecast Chinese customers’ acceptance of internet banking. It will give benefits to bank and society on paying attention to the influence of social network for internet banking in China.